2015
DOI: 10.1039/c5cc04548g
|View full text |Cite
|
Sign up to set email alerts
|

Facet-dependent acidic and catalytic properties of sulfated titania solid superacids

Abstract: Sulfated titania solid superacids with dominant {001}, {001}/{101}, and {101} facets were prepared by the hydrothermal method and subsequent sulfation. Their facet-dependent acidic properties were investigated by the solid-state (31)P NMR technique and Pechmann condensation of 5,7-dihydroxy-4-methyl coumarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…The broadening of the peaks indexed to (004) facets in T001 and T101/001 diffraction patterns is ascribed to the decrease of crystallite size in the direction perpendicular to {001} facets. In addition, the narrowing of peaks attributed to (200) facets in T001 is caused by the increase of the crystallite size in the direction perpendicular to {100} facets, and this is in good accordance with the shape of T001 samples as nanosheets shown in Figure a . Compared with T001 and T101/001 samples, the broadening of the peak indexed to (101) facets indicates the decrease of crystallite size in the direction perpendicular to {101} facets in T101 sample.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The broadening of the peaks indexed to (004) facets in T001 and T101/001 diffraction patterns is ascribed to the decrease of crystallite size in the direction perpendicular to {001} facets. In addition, the narrowing of peaks attributed to (200) facets in T001 is caused by the increase of the crystallite size in the direction perpendicular to {100} facets, and this is in good accordance with the shape of T001 samples as nanosheets shown in Figure a . Compared with T001 and T101/001 samples, the broadening of the peak indexed to (101) facets indicates the decrease of crystallite size in the direction perpendicular to {101} facets in T101 sample.…”
Section: Resultssupporting
confidence: 77%
“…10 nm. The percentage of {001} facets is estimated to be less than 10% on T101 samples [17a]. The lattice fringes with d‐spacings of 0.24, 0.19 and 0.35 nm are in accordance with (004), (200) and (101) planes of anatase TiO 2 , respectively, as found in Figure f.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Many SACs, such as solid superacids, strong acidic cation‐exchange resin and −SO 3 H‐functionalized carbon materials have been synthesized and used in acid‐catalyzed reactions . Among all these catalysts mentioned above, carbon‐based solid acid catalysts (CBSACs) with outstanding hydrothermal, mechanical and catalytic properties have received numerous attentions recently .…”
Section: Introductionmentioning
confidence: 99%
“…However,i ti sr are to see the studyo nt he acidic properties after sulfationo fm etal oxidesw ith specific exposed facets.I n the previous research we reported sulfated TiO 2 solid superacids and found their acidic and catalytic properties are facetdependent. [10] In this work, three different Cu 2 Om icrocrystals with various morphologies were preparedi ncluding octahedra with dominant {111}f acets, cuboctahedra with both {100} and {111} facets, and cubes with dominant {100} facets. These Cu 2 Os amples were sulfated and 31 PMAS NMR was used to study their acid properties with trimethylphosphine (TMP) as the probe molecule.…”
mentioning
confidence: 99%